КОМПЛЕКСНОЕ ЛЕЧЕНИЕ ДУОДЕНАЛЬНЫХ ЯЗВ В ГАСТРОЭНТЕРОЛОГИЧЕСКОМ ОТДЕЛЕНИИ МЦ ГМУ Г.СЕМЕЙ С ИСПОЛЬЗОВАНИЕМ ЭНДОСКОПИЧЕСКИХ ПРОЦЕДУР («Наука и здравоохранение», 2026)
Research objective is the improvement of a clinical course of ulcer at patients with duodenal localization in by means of acombination of local treatment and system immune modulation use.144 patients with ulcer disease with duodenal defect localization are surveyed.As local treatment applications of film-forming glue, including with deposition under a film of medical products Metronidazol and De-nol were applied.Clinical results of the developed treatment exceeded those for complex conservative therapy and were authentic both inrespect of normalization of subjective indicators, and at the analysis of objective results dynamic endoscopic inspections.